Morfometrik Usus dan Performa Ayam Broiler yang Diberi Cekaman Panas dan Ekstrak n-Heksana Kulit Batang “Jaloh" (Salix tetrasperma Roxb) - . Sugito; W Manalu; D A Astuti; . Chairul (Media Peternakan, 2007)
The n-hexane fraction of “jaloh" extract could reduce detrimental effects of heat stress on broiler chicken. An experiment was conducted to study morphometric of small intestine villi (duodenum, jejunum, and ileum) and performances of broiler exposed to heat stress on 33±1oC for 4 hours/day and given extract n-hexane of “jaloh" bark (EHJ) with doses 5, 10, and 20 mg/kg body weight (BW). Thirty broilers aged 20 days (Cobb strain) were randomly divided into 5 groups of treatments. The first treatment group was external control namely chickens without heat stress and without EHJ administration (tCP). The second group of treatment was internal control representing chickens exposed to heat stress without EHJ administration (CP). The third, fourth, and fifth treatment groups consisted of chickens exposed to heat stress and given 5 (CP+EHJ5), 10 (CP+EHJ10), and 20 mg/kg BW of EHJ (CP+EHJ20), respectively. Heat stress and “jaloh" extract were implemented every day. “Jaloh" extracts were given 1 hour before temperature in the cage was raised. Results showed that heat stress decreased weight gain and height of jejunum villi, and increased feed conversion ratio. The dose of 10 mg/kg BW of EHJ can improve performance of broiler chickens and morphometric of small intestine villi. Key words: heat stress, Salix tetrasperma, performance, broiler